The open method of coordination (OMC) as an evolutionary learning process - Ana B. Ania; Andreas Wagener (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2009)
We interpret the Open Method of Coordination (OMC), recently adopted by the EU as a mode of governance in the area of social policy and other fields, as an imitative learning dynamics of the type considered in evolutionary game theory. The best-practise feature and the iterative design of the OMC correspond to the behavioral rule 'imitate the best.' In a redistribution game with utilitarian governments and mobile welfare beneficiaries, we compare the outcomes of imitative behavior (long-run evolutionary equilibrium), decentralized best-response behavior (Nash equilibrium), and coordinated policies. The main result is that the OMC allows policy coordination on a strict subset of the set of Nash equilibria, favoring in particular coordination on intermediate values of the policy instrument.
Keywords: H77; H75; C73; 330; Open Method of Coordination; Finite-population Evolutionarily Stable Strategy; Imitation; Mobility; Redistribution; EU-Politik; Internationale wirtschaftspolitische Koordination; Evolutionäre Spieltheorie; Theorie; EU-Staaten